Salivary Fractalkine Differentiating Periodontitis from Periodontally Healthy Subjects - Omer Mohammed Harbood; Raghad Fadhil Abbas (International Journal of Dentistry)
Objective. The chemokine “Fractalkine” (CX3CL1) and its corresponding receptor (CX3CR1), chemokine belonging to the CX3C family, have an essential role in developing several systemic inflammatory disorders. Accordingly, the proliferation, adhesion, and migration of inflammatory cells are all affected by it. In light of this, the present study attempts to address the following questions: (1) Is the salivary level of fractalkine and its receptor associated with periodontitis patients with different severities? (2) Is it possible to distinguish periodontitis from periodontally healthy subjects? Methods. This study included 30 individuals who had been considered controls, having healthy periodontium, and 90 patients with varying stages of periodontitis. The patients were equally divided into three groups: those with Stage I, Stage II, and Stage III. After each subject’s saliva was collected, periodontal markers including bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment loss (CAL) were recorded. Enzyme-linked immunosorbent assays (ELISA) were used to detect the protein levels of salivary CX3CL1 and CX3CR1. Results. In comparison to the control group, patients with periodontitis had statistically increased salivary concentrations of CX3CL1 and CX3CR1 (P <0.001). Additionally, all clinical periodontal indicators (BOP, PPD, and CAL) had a strong association with salivary CX3CL1 and CX3CR1 levels. Furthermore, by using the ROC (receiver operating characteristic), both biomarkers showed a good ability to differentiate periodontitis from periodontally healthy subjects, and an excellent ability to distinguish Stage I and Stage III periodontitis from periodontally healthy subjects. The AUC for salivary CX3L1 and its receptors, CX3R, was 0.93 and 0.8, respectively, to distinguish Stage I from patients with good periodontal health. In contrast, the biomarkers’ AUC for separating individuals with Stage III periodontitis from those in healthy periodontal conditions was 1. Conclusion. Fractalkine and its receptor are linked to periodontitis and may distinguish between periodontitis and healthy periodontal tissues, suggesting its role as a possible part of periodontal disease pathogenesis.